59.6k views
1 vote
Enter the correct answer in the box.

Consider the system of equations.
3x + 2y = 23
1/2x - y = 4

Rewrite the first equation in slope-intercept form to find an expression that can be substituted for Y in the second equation.

User Lightbeard
by
5.2k points

2 Answers

4 votes

Answer:

y=-3x/2+23/2 is the answer

Explanation:

i know cause i just did it on Plato thats the answer it gave me

User GaTechThomas
by
6.0k points
6 votes

Answer:

Slope-intercept form: y = (-3/2)x + 11.5

Explanation:

The first equation, 3x + 2y = 23, is in the standard form of a function ( Ax + By = C). In order to convert to slope-intercept form (y = mx + b), you can use the standard form equation and simply solve for the variable 'y'. Using inverse operations to isolate the variable, we would first subtract '3x' from both sides of the equation: 3x - 3x + 2y = 23 - 3x or 2y = -3x + 23. Next, we need to divide all terms by 2 in order to get rid of the coefficent in front of 'y': 2y/2 = (-3/2) x + (23/2) or y = (-3/2)x + 11.5. You can then use this expression of 'y' to substitute for the value of 'y' in the second equation.

User Sandeep Modak
by
5.4k points